Mortality and functional outcomes of endovascular stroke therapy in the United States. Issue 3 (16th November 2020) - Alqahtani, Fahad; Osman, Mohammed; Harris, Alyssa Hartsell; Hohmann, Samuel F.; Alkhouli, Mohamad
Abstract: Background: We sought to evaluate the nationwide trends in the characteristics and outcomes of for endovascular stroke therapy in contemporary practice. Methods: We selected patients with acute ischemic stroke who underwent endovascular stroke therapy between 01 October 2015 and 30 September 2019 in a large academic consortium database. The end points of this study were (a) in‐hospital mortality and functional outcomes and, (b) predictors of poor functional outcome, defined as death or discharge to hospice, or to a long‐term nursing facility. Results: Among the 22, 193 included patients; 50.3% were females, and 66.5% were white. Mean age was 68±15 years. Poor functional outcomes occurred in 8, 274 patients (37.4%), of whom 2, 741 (12.4%) died in the hospital, 1, 345 (6.1%) were discharged to hospice, and 4, 188 (18.9%) were discharged to other long‐term facilities. Most common in‐hospital complications were mechanical ventilation (32.3%), intracranial hemorrhage (18.9%), and acute kidney injury (15.6%). Median total and intensive‐care length‐of‐stay were 7 days (IQR = 4–9), and 2 days (IQR = 1–4), respectively. Median cost was $36, 609 (IQR = $26, 034–$54, 313). In a multi‐logistic regression analysis; age, hypertension, diabetes, anemia, heart failure, vascular disease, chronic pulmonary disease, renal insufficiency, Medicare/medicaid insurance, transfer from nonendovascular capable hospital, and low procedural volume independently predicted poor functional outcomes. Tissue plasminogen activator use was associated with better functional outcomes. Conclusion: There is a substantial growth in the performance of endovascular stroke interventions in the United States in recent years, and those were associated with favorable short‐term outcomes.